2022
DOI: 10.3389/fnins.2022.952322
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural connectome in neonates with prenatal opioid exposure

Abstract: IntroductionInfants with prenatal opioid exposure (POE) are shown to be at risk for poor long-term neurobehavioral and cognitive outcomes. Early detection of brain developmental alterations on neuroimaging could help in understanding the effect of opioids on the developing brain. Recent studies have shown altered brain functional network connectivity through the application of graph theoretical modeling, in infants with POE. In this study, we assess global brain structural connectivity through diffusion tensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Regional, bulk cell-type, and single cell sequencing are likely to highlight more specific pathways in the future, for example, in the dopamine and microglial systems. We conclude that in utero or early post-natal exposure to specific opioids has the capacity to impact neuronal circuity ( Salzwedel et al, 2020 ; Radhakrishnan et al, 2022 ; Vishnubhotla et al, 2022 ) with long-lasting effects in select behaviors that outlast the alterations to gene activation. The comparisons of perinatal and adult datasets highlight the large number of diverse genes that contribute to various pathways, so that phenotypic responses may overlap considerably more than transcriptional responses.…”
Section: Discussionmentioning
confidence: 90%
“…Regional, bulk cell-type, and single cell sequencing are likely to highlight more specific pathways in the future, for example, in the dopamine and microglial systems. We conclude that in utero or early post-natal exposure to specific opioids has the capacity to impact neuronal circuity ( Salzwedel et al, 2020 ; Radhakrishnan et al, 2022 ; Vishnubhotla et al, 2022 ) with long-lasting effects in select behaviors that outlast the alterations to gene activation. The comparisons of perinatal and adult datasets highlight the large number of diverse genes that contribute to various pathways, so that phenotypic responses may overlap considerably more than transcriptional responses.…”
Section: Discussionmentioning
confidence: 90%
“…A significant challenge is distinguishing the neurobiological effects of opioid agonists from various other confounding factors, including tobacco, alcohol, nonmedical drugs, environmental influences, and additional medical risks ( Logan et al, 2013 ; Radhakrishnan et al, 2022a ; Radhakrishnan et al, 2022b ). The effects of opioids during pregnancy extend beyond nociceptive processes to include effects on gastrointestinal, endocrine, and autonomic functions as well as cognition, behavior, and reward circuitry for the mother and developing fetus, and subsequently the offspring ( Radhakrishnan et al, 2021 ; Radhakrishnan et al, 2022a ; Radhakrishnan et al, 2022b ; Radhakrishnan et al, 2022c ; Vishnubhotla et al, 2022 ; Wise et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated that perinatal exposure to opioids can lead to long-lasting consequences such as cognitive deficits and sensorimotor impairments ( Mactier and Hamilton, 2020 ). Recent imaging studies have also reported low-term changes in neural functioning after opioid exposure ( Radhakrishnan et al, 2022 ; Vishnubhotla et al, 2022 ). These studies, however, were primarily focused on heroin and methadone and may not represent the effects of high-potency synthetic opioids like fentanyl.…”
Section: Introductionmentioning
confidence: 99%